Need Analysis Of English for Specific Purpose (ESP) for Nursing Students at Stikes Eka Harap Palangka Raya - Nata, Ipan Dwi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to describe the English language needs of Nursing students at STIKES Eka Harap Palangka Raya. Needs analysis in English language teaching and learning focuses on targets and learning needs. To teach and learn nursing English, it is very important to be aware of the needs of the students, their background knowledge of English, especially in the context of nursing and the demands of the target where students will work professionally as nurses. ESP is an English language teaching approach with a focus on the needs of English language learners. With ESP, learning and teaching English is expected to facilitate students to be more focused and easier to communicate in the field of they are studying. The data collection techniques used were questionnaires for 42 students, and direct interviews with English lecturer and Nursing lecturer. The analysis results of English language needs for nursing students: The importance of learning English to improve and do communication that can be applied in conversation or practice contexts. English material related to English terms relevant to the field of nursing was the learning target. Other materials that were applicable in improving listening and speaking skills were also learning priorities. Various learning methods of teaching English for nursing students were options that must be designed by the lecturer. It was hoped that the research results would become a reference for the syllabus design and development, especially for English courses.